Correlation of peripheral white cell and bone marrow changes with folate levels in pregnancy and their clinical significance. Issue 1 (January 1966) - Varadi, S.; Abbott, D.; Elwis, A.
Abstract : Two hundred and thirty-eight `megaloblastic' pregnancies are reviewed. Bone-marrow aspiration was performed in every case. Serum folate estimations were strongly suggestive of folic acid deficiency in only 34% of cases. If, however, the red cell folate was determined as well, there was an almost complete agreement with the changes in the erythroblasts. It is suggested that hyper-segmentation of the neutrophils in association with a diminished red cell folate level is indicative of significant folic acid deficiency. This series possibly shows a slight but statistically insignificant increase of accidental haemorrhage. No effect on birth weight or incidence of stillbirth was demonstrable.